2001
DOI: 10.1177/104063870101300506
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Bovine Mammary Gland Health Status by Somatic Cell Counting, Flow Cytometry, and Cytology

Abstract: Abstract. Bovine mastitis phases induced by Staphylococcus aureus were assessed in 6 lactating cows before challenge and at 1, 4-8, and 9-14 days postinoculation (dpi). Milk lymphocytes, macrophages, and polymorphonuclear cells (PMN) were counted by conventional (manual) cytology, identified by CD3ϩ and CD11bϩ immunofluorescence and counted by flow cytometry (based on leukocyte forward and side light scatter values). Somatic cell counts (SCC) and recovery of bacteria were recorded at the same times. Preinocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
64
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 33 publications
8
64
0
17
Order By: Relevance
“…Our results showed that the cows with CM had distinctly increased DNA methylation level in CD4 promoter but downregulated expression of the gene in the peripheral blood cells of Chinese Holstein cows, while healthy cows showed the opposite. The negative correlation of DNA methylation and CD4 expression was consistent with the significant decrease in CD4 + T cells observed in the cows with mastitis (Rivas et al, 2001;Rivas et al, 2007). Thus DNA methylation level of CD4 promoter could be a helpful molecular marker for selection against mastitis in dairy cattle.…”
Section: Discussionsupporting
confidence: 62%
“…Our results showed that the cows with CM had distinctly increased DNA methylation level in CD4 promoter but downregulated expression of the gene in the peripheral blood cells of Chinese Holstein cows, while healthy cows showed the opposite. The negative correlation of DNA methylation and CD4 expression was consistent with the significant decrease in CD4 + T cells observed in the cows with mastitis (Rivas et al, 2001;Rivas et al, 2007). Thus DNA methylation level of CD4 promoter could be a helpful molecular marker for selection against mastitis in dairy cattle.…”
Section: Discussionsupporting
confidence: 62%
“…A CCS diferencial permite a diferenciação das populações celulares presentes no leite e, desta forma, possibilita a detecção da mastite logo no início do processo infeccioso, quando a CCS ainda é baixa (Rivas et al, 2001;Dosogne et al, 2003;Koess e Hamann, 2008). Entre os métodos aplicados para a contagem diferencial de leucócitos, podem-se citar a contagem microscópica direta por esfregaços, a técnica de citocentrifugação e a citometria de fluxo.…”
Section: Discussionunclassified
“…A técnica de citocentrifugação apresenta as vantagens da rapidez de sua execução e da menor variabilidade em relação à contagem direta em esfregaços (Dulin et al, 1982). Do mesmo modo, a contagem diferencial pela citometria de fluxo tem sido associada à maior repetibilidade devido ao expressivo número de células avaliadas (Rivas et al, 2001;Dosogne et al, 2003;Koess e Hamann, 2008).…”
Section: Discussionunclassified
See 2 more Smart Citations